Magnetite drives microbial community restructuring and stimulates aceticlastic methanogenesis of type II Methanosarcina in mangrove sediments - Jinjie Zhou; Cui-Jing Zhang; Dayu Zou; Chengxiang Gu; Meng Li (Microbiome)
Abstract Background Mangrove wetlands are critical hotspots of methane emissions, yet the role of naturally occurring minerals in shaping their microbial communities and methanogenic processes is poorly understood. Magnetite, a common iron mineral in soils and sediments, has been reported to enhance aceticlastic methanogenesis and facilitate syntrophic methanogenesis. In this study, we integrated multi-omic profiling with cultivation-based approaches to investigate the impact of magnetite on methanogenesis of microbial consortia derived from mangrove sediments, using lactate as a substrate. Results Across five serial transfers, mangrove microbial consortia converted lactate to propionate and acetate, which were subsequently degraded into methane. Magnetite addition significantly stimulated methane production, leading to notable changes in community structure, particularly for aceticlastic methanogens, with Methanosarcina predominating in the magnetite-amended cultures and Methanothrix in controls. Four Methanosarcina strains T3, T4, T13, and MeOH were subsequently isolated from magnetite-amended cultures. Combined analyses of metagenome-assembled genomes and the genomes of these isolates revealed that the enriched Methanosarcina in magnetite-amended cultures belonged to type II deficient in hydrogenotrophic methanogenesis pathway. Metatranscriptomic analyses suggested that magnetite addition stimulated aceticlastic methanogenesis of type II Methanosarcina and hydrogenotrophic methanogenesis of Methanomicrobiales in the consortia. Furthermore, pure culture experiments confirmed that magnetite stimulated aceticlastic methanogenesis by Methanosarcina sp. T3, although its gene expression patterns differed from those observed in the microbial consortia. Additionally, Methanofastidiosales, an uncultured archaeal lineage possessing H2-dependent methylotrophic methanogenesis, was detected in all transfers. Conclusions Our findings demonstrate that magnetite alters methanogenic consortia in mangrove sediments, selectively stimulating aceticlastic methanogenesis of type II Methanosarcina and modulating hydrogenotrophic activity in Methanomicrobiales. By integrating multi-omics analyses with pure culture validation, we demonstrate, for the first time, that magnetite directly enhances the aceticlastic methanogenesis of type II non-hydrogenotrophic Methanosarcina. This study provides new insights into the influence of magnetite on complex microbial consortia, offers a deeper understanding of the physiology of type II non-hydrogenotrophic Methanosarcina, and advances knowledge of mineral-mediated regulation of methanogenic networks in anoxic environments. Video Abstract